Preparation method of carbon quantum dot modified enzyme response type wood preservative
By using carbon quantum dot modifier enzyme-responsive preservatives in wood preservatives, the toxicity, soluble and easy loss problems of traditional wood preservatives are solved, and a longer efficacy and higher fixation effect is achieved, which enhances the Inhibiting fungi.
Patent Information
- Application Number
- CN202411595567.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-14
AI Technical Summary
Traditional wood preservatives have problems such as toxicity, soluble, easy to lose, short potency and poor fixation, which limits their application in the field of wood protection.
The preparation method of carbon quantum dot modifier enzyme-responsive wood preservatives is used, hollow mesoporous silica microspheres (HMON) are used as carriers, garlic nanoparticles are used as guest molecules, and carbon quantum dots are used as gated molecules, and hydrothermal methods are synthesized The lignin carbon quantum dots are blocked to form the enzyme-responsive preservative HMON-garlic NPs-CQDs.
It improves the effectiveness time, utilization rate and fixation effect of preservatives, extends the efficacy of preservatives, enhances the ability to inhibit fungi, and reduces the waste of preservatives.
Smart Images

Figure CN119304975A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preservative preparation, and specifically relates to a method for preparing a carbon quantum dot-modified enzyme-responsive wood preservative. Background Art
[0002] As a biomass material, wood is very easy to decay. After being corroded by decay fungi, the structure, performance and chemical composition of wood will change, and its macroscopic characteristics such as mechanical properties and wood color will change. As the decay intensifies, the density and compressive strength of decayed wood will also decrease. Wood preservatives can extend the service life of wood. However, the use of traditional preservatives to treat wood makes wood lose some competitiveness due to its certain toxicity. Wood impregnated with preservatives contains toxic chemicals, such as pentachlorophenol, etc. After burning, the preservatives in the wood will be released into the ecosystem, thereby polluting the environment. With the increase of public risk awareness and the proposal of the concept of green development, the development of environmentally friendly antiseptic technologies and processes has been further promoted, and researchers are increasingly considering the use of natural products to protect wood. Natural compounds such as essential oils, heartwood extracts, waxes, resins, bark and tannins show good prospects in wood protection. As an alternative to chemical preservatives, wood preservatives extracted from natural sources have been widely studied because they are generally harmless and non-toxic to humans and animals.
[0003] Although plant extracts have the advantages of wide sources and environmental protection, they still have some shortcomings from a holistic perspective, such as plant-based preservatives are easily soluble in water, easy to lose, short efficacy period, high cost and poor fixation. With the advancement of science and technology, wood preservation processes and technologies are also constantly innovating. Most of the traditional plant-based preservatives for treating wood use direct toxicity preservation. Toxic preservation relies on the toxicity of preservatives to directly inhibit decay fungi. Most commonly used preservatives achieve wood preservation through toxicity. Direct toxicity preservation will lead to the above-mentioned shortcomings. Plant-based preservatives have the disadvantages of large dosage, short efficacy period, and easy loss, which limits their application in the field of wood protection. Most of the current wood preservative treatment processes use direct impregnation methods. Direct impregnation of plant-based preservatives will increase the waste of wood preservatives and will not extend the effective period of preservatives. When wood decay fungi grow, they will release highly active laccases. Therefore, a method for preparing a carbon quantum dot-modified enzyme-responsive wood preservative is proposed to solve the above problems. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a carbon quantum dot-modified enzyme-responsive wood preservative to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions: 1. A method for preparing a carbon quantum dot modified enzyme-responsive wood preservative, characterized in that it comprises the following steps:
[0006] S1: Measure 12 mL of ultrapure water, 80 mL of anhydrous ethanol and 3.6 mL of concentrated ammonia solution, and stir for a preset time to fully mix them;
[0007] Add 6.2 mL of TEOS, stir at room temperature for 2 h, centrifuge, take the precipitate, centrifuge and wash it three times with the preset liquid, dissolve the obtained precipitate SiO2 in 70 mL of ultrapure water to obtain SiO2 solution for use;
[0008] Weigh 1.90 g CTAC and 0.05 g TEA and add them to 100 mL ultrapure water. Stir magnetically to fully dissolve them. Continue stirring for 2 h. Add 35 mL of the previously prepared SiO2 solution and stir magnetically. Then, add 2 mL of BTES to the above solution at 80 °C and stir for 2 h. Centrifuge for 5 min under the same conditions. Take the precipitate and wash it twice with the preset liquid in sequence.
[0009] 0.6M Na2CO3 was added to the above solution and stirred at 80°C for 2h. The solution was washed three times by centrifugation at 8000r / min with a preset liquid. Finally, the solid product was extracted with a methanol solution dissolved in NaCl and stirred at room temperature overnight to remove the CTAC template. After centrifugal washing, the product was freeze-dried to obtain HMON nanoparticles.
[0010] S2: Weigh 200.00 mg of HMON nanoparticles, dissolve in 60 mL of ultrapure water, and after uniform dispersion, add 450 μL of APTES reagent, stir at room temperature for 10 h, centrifuge three times with ultrapure water, and freeze-dry to obtain amino-functionalized HMON (HMON-NH2);
[0011] S3: Weigh 75.00 g of crushed garlic paste and dissolve it in 250 mL of ultrapure water and soak it for 2 h. Cook it at a preset temperature for 10 min and filter it with gauze to obtain a crude garlic extract. Mix 1 mL of garlic extract, 0.09 g of C2H8N2, 1.00 g of urea and 9 mL of ultrapure water and microwave it to obtain brown solid granular garlic NPs.
[0012] S4: adding the garlic NPs prepared in S3 to ultrapure water, preparing a garlic NPs aqueous solution of a certain concentration with ultrapure water, dissolving HMON-NH2 in ultrapure water, dispersing evenly, adding to the garlic NPs aqueous solution, stirring at room temperature for 12 h, removing the supernatant after centrifugation, washing with ultrapure water for 3 times, and freeze-drying to obtain hollow mesoporous microspheres HMON-garlic NPs loaded with garlic NPs;
[0013] S5: 60 mL of anhydrous ethanol was measured and placed in a 250 mL beaker, 2.15 g of dealkalized lignin was added, and the mixture was stirred at 1000 r / min for 10 min. After that, the mixture was evenly dispersed by ultrasound for 15 min, and the mixture was placed in a hydrothermal reactor for hydrothermal reaction to obtain a crude solution of carbon quantum dots. The solution was filtered 3 times to remove solid impurities, and the supernatant was filtered through a filter membrane after centrifugation. The filtrate was dialyzed with ultrapure water for 48 h, and then dried in a drying device to obtain lignin carbon quantum dots CQDs.
[0014] S6: Weigh 0.30 g of HMON-garlic NPs powder obtained in S4, place it in a 500 mL beaker, add 200 mL of ultrapure water, and stir for 30 min. Dissolve 0.15 g of lignin carbon quantum dots in 100 mL of ultrapure water, disperse it evenly by ultrasonication, add it to the HMON-garlic NPs solution, and continue stirring at room temperature for 48 h. Synthesize the enzyme-responsive preservative HMON-garlic NPs-CQDs, and use lignin CQDs as a pore plugging agent to block the HMON surface.
[0015] Preferably, in S1, the centrifugal treatment is carried out at a centrifugal rate of 10000 r / min and for a centrifugal time of 5 min.
[0016] Preferably, in S3, the power of the microwave treatment is 500 W and the centrifugation time is 5 min.
[0017] Preferably, in S4, the centrifugal treatment is carried out at a centrifugal rate of 8000 r / min and for a centrifugal time of 10 min.
[0018] Preferably, in S5, the centrifugal treatment is carried out at a centrifugal speed of 8000 r / min and a centrifugal time of 15 min.
[0019] Preferably, in S5, the drying equipment is a constant temperature drying oven, and the drying temperature of the constant temperature drying oven is 60°C.
[0020] Preferably, in S5, the filtration accuracy of the filter membrane is 0.22 μm.
[0021] Preferably, in S1, the preset liquid includes ethanol and ultrapure water.
[0022] Preferably, in S1, the stirring time of the magnetic stirring is 1.5 h.
[0023] Preferably, in S5, the reaction temperature of the hydrothermal reaction is 180° C., and the reaction time is 8 h.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] Since carbon quanta have excellent water solubility, biocompatibility and fluorescence properties, they have great development potential in the fields of bio-labeling / imaging, sensor design and photocatalysis. Therefore, in the design process of the enzyme-responsive preservative HMON-garlic NPs-CQDs, the present invention explores the possibility of CQDs as a mesopore plugging agent and confirms the feasibility of the constructed enzyme-responsive preservative. CQDs can be anchored in the mesopores of HMON and block the guest molecule garlic NPs inside the HMON to prevent the premature leakage of garlic NPs, improve the antiseptic effect, control the release of active ingredients, prolong the duration of the preservative, and improve the utilization rate of the preservative. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 TEM image (a) and particle size distribution diagram (b) of lignin carbon quantum dots of the present invention;
[0027] Figure 2 Transmission electron microscope images of microspheres at different synthesis stages of the present invention (a, b) SiO2; (c) SiO2 surface coated with silicon shell; (d, e, f) HMON images;
[0028] Figure 3 Transmission electron microscopy images of HMON-garlic NPs and HMON-garlic NPS-GQDs of the present invention (a) HMON-garlic NPs; (b, c) HMON-garlic NPs-CQDs;
[0029] Figure 4 This is a growth photo of Coriolus versicolor after adding HMON-garlic NPs-CQDs in the present invention at 6 days;
[0030] Figure 5 This is a SEM picture of the distribution of HMON-garlic NPs-CQDs in wood;
[0031] Figure 6 Schematic diagram of drug loading and loss rate of garlic NPS and HMON-garlic NPs-CQDs of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] See also Figure 1-Figure 6 As shown, the present invention provides the following technical solutions:
[0034] The responsive release of preservatives provides a new idea for solving the problems of easy waste of preservatives and easy loss of antibacterial ingredients in the field of wood protection. The present invention uses hollow mesoporous silica microspheres (HMON) as preservative carriers, garlic NPs as guest molecules, and carbon quantum dots as gating molecules to encapsulate HMON microspheres loaded with garlic NPs, and finally successfully synthesizes enzyme-responsive preservatives HMON-garlic NPs-CQDs. In the synthesis stage, since the surface of HMON is easy to functionalize, an aminosilanization agent is introduced to modify the surface of HMON to form HMON-NH2. Lignin is used as a reaction carbon source, and lignin carbon quantum dots are synthesized under hydrothermal conditions. The synthesized carbon quantum dots are used as blocking agents to effectively block HMON-garlic NPs microspheres loaded with garlic NPs to form enzyme-responsive preservatives HMON-garlic NPs-CQDs, and the controlled release behavior of the system under different enzyme concentrations is analyzed by in vitro release tests. In addition, the inhibitory effect of HMON-garlic NPs-CQDs on the biological activity of Coriolus versicolor was investigated, and the effect of enzyme-responsive preservatives on the corrosion resistance of wood was evaluated, in order to provide new methods and ideas for the intelligent application of enzyme-responsive preservatives in the field of wood protection. The following implementation methods are provided: Specific implementation method 1
[0036] S1: Solution preparation and SiO2 preparation: Measure 12mL ultrapure water, 80mL anhydrous ethanol and 3.6mL concentrated ammonia solution in an accurate amount, stir at a moderate speed on a magnetic stirrer for 30 minutes until completely mixed. Then add 6.2mL TEOS and continue stirring at room temperature for 2 hours. Treat at a centrifugal rate of 10000r / min for 5 minutes and take the precipitate. After washing with ethanol and ultrapure water alternately by centrifugation for 3 times, dissolve the precipitated SiO2 in 70mL ultrapure water for later use.
[0037] S2: Synthesis of HMON nanoparticles: Weigh 1.90g CTAC and 0.05g TEA, add to 100mL ultrapure water, and stir magnetically for 1.5 hours until completely dissolved. Add 35mL of the previously prepared SiO2 solution and continue magnetic stirring. At 80°C, slowly add 2mL BTES and stir for 2 hours. Centrifuge for 5 minutes under the same conditions, take the precipitate and wash it twice with ethanol and ultrapure water in turn. Then, add 0.6MNa2CO3 to the solution and stir at 80°C for 2 hours. After centrifugation and washing 3 times at 8000r / min, extract with methanol solution containing NaCl and stir at room temperature overnight. Finally, centrifuge, wash and freeze-dry to obtain HMON nanoparticles.
[0038] S3: Preparation of HMON-NH2: 200.00 mg of HMON nanoparticles were dissolved in 60 mL of ultrapure water, and after being evenly dispersed, 450 μL of APTES reagent was added and stirred at room temperature for 10 hours. After centrifugation with ultrapure water for 3 times, the amino-functionalized HMON (HMON-NH2) was obtained by freeze drying.
[0039] S4: Preparation of garlic NPs: 75.00 g of crushed garlic paste was dissolved in 250 mL of ultrapure water and soaked for 2 hours, boiled at 90 °C for 10 minutes, and filtered through gauze to obtain the crude garlic extract. 1 mL of garlic extract, 0.09 g of C2H8N2, 1.00 g of urea and 9 mL of ultrapure water were mixed, treated at 500 W microwave power for 5 minutes, and brown solid granular garlic NPs were obtained after centrifugation.
[0040] S5: Preparation of HMON-garlic NPs: Dissolve the prepared garlic NPs in an appropriate amount of ultrapure water to adjust the concentration. Dissolve HMON-NH2 in ultrapure water, evenly disperse it, and add it to the garlic NPs aqueous solution. Stir at room temperature for 12 hours. Centrifuge at 8000r / min for 10 minutes, remove the supernatant, wash it with ultrapure water three times, and freeze-dry it to obtain HMON-garlic NPs.
[0041] S6: Preparation of lignin CQDs: Add 60 mL of anhydrous ethanol to a 250 mL beaker, then add 2.15 g of dealkalized lignin, stir at 1000 r / min for 10 minutes, and ultrasonicate for 15 minutes to make it evenly dispersed. Heat the hydrothermal reactor to 180 ° C, put the mixed solution in and react for 8 hours to obtain a crude solution of carbon quantum dots. After filtration 3 times, centrifuge and filter the supernatant with a 0.22 μm filter membrane. The filtrate was dialyzed with ultrapure water for 48 hours, and then dried in a constant temperature drying oven at 60 ° C to obtain lignin carbon quantum dots CQDs.
[0042] S7: Synthesis of preservative: 0.30 g HMON-garlic NPs powder was added to 200 mL ultrapure water and stirred for 30 minutes. 0.15 g lignin CQDs was dissolved in 100 mL ultrapure water, added to the HMON-garlic NPs solution after ultrasonic dispersion, and stirred at room temperature for 48 hours to synthesize HMON-garlic NPs-CQDs preservative. Lignin CQDs were used as pore plugging agents to plug the HMON surface. Specific implementation method 2
[0044] Based on method 1, adjust some parameters:
[0045] The magnetic stirring time was increased to 2 h in S1 to ensure that the components were fully mixed.
[0046] In addition, in S3, the microwave treatment power was adjusted to 400 W to observe the effect of power variation on the formation of garlic NPs.
[0047] Furthermore, in this embodiment, in S5, the hydrothermal reaction temperature is increased to 200°C, and the reaction time is shortened to 6 hours to explore the generation efficiency of lignin CQDs at a higher temperature.
[0048] In addition, in S6, during the preservative synthesis stage, the stirring time at room temperature was extended to 72 h to enhance the interaction between the components. Specific implementation method three
[0050] Further optimization of the preparation process:
[0051] S1: The centrifugal treatment was changed to 12000r / min and the centrifugal time was kept at 5 minutes to improve the precipitation efficiency.
[0052] S3: When preparing the crude garlic extract, the cooking temperature was adjusted to 85 °C to study the effect of temperature on the extraction of active ingredients in garlic.
[0053] S4: During the preparation of HMON-garlic NPs, a small amount of surfactant was added to improve the dispersibility and reduce agglomeration.
[0054] S5: After the preparation of lignin CQDs, an additional UV treatment step was added to explore its effect on the optical properties of CQDs.
[0055] S6: In the final stage of preservative synthesis, ultrasonic treatment was introduced to promote the uniform distribution of CQDs on the surface of HMON-garlic NPs. Specific implementation method four
[0057] Explore the effects of different raw material ratios on preservative performance:
[0058] S1: Adjust the ratio of TEOS, CTAC, TEA and other raw materials to observe the effect on the morphology and structure of HMON nanoparticles.
[0059] S3: Change the ratio of garlic extract to other additives to evaluate their effects on the formation and properties of garlic NPs.
[0060] S5: Adjust the ratio of dealkalized lignin to anhydrous ethanol to study its effect on the yield and quality of lignin CQDs.
[0061] S6: During the preservative synthesis stage, the ratio of HMON-garlic NPs to lignin CQDs was adjusted to find the optimal ratio to achieve the best preservative effect.
[0062] In addition, in the present invention, the lignin carbon quantum dots were synthesized by a one-step green hydrothermal method using dealkalized lignin as a precursor. The morphology, distribution and particle size of the lignin carbon quantum dots were characterized by TEM. Figure 1As shown. Figure 1 As can be seen in (a), lignin CQDs have good dispersion and uniform particle size distribution, showing a spherical structure without obvious particle agglomeration. The lattice fringe structure can be clearly seen in the inset in the upper right corner of the figure. The fringe spacing is 0.34nm, corresponding to the crystal plane (002) of graphite carbon, indicating that lignin CQDs have a high degree of graphitization. The particle size of lignin CQDs was analyzed using nanoparticle distribution statistical software. Figure 1 (b) It can be seen that the particle size distribution is relatively uniform, ranging from 2.5 to 6.0 nm, with an average particle size of 3.92 ± 0.03 nm, which is relatively large compared with garlic NPs. TEM tests showed that dealkalized lignin formed a graphite-like structure during the hydrothermal carbonization process, proving the synthesis of lignin CQDs.
[0063] like Figure 2 As shown in the figure, the morphological characteristics of three samples, SiO2 microspheres, SiO2 microspheres coated with silicon shells and HMON, are shown in the transmission electron microscope. Figure 2 As can be seen in (a, b), the SiO2 microspheres present a regular circular structure with uniform outer diameter, a relatively smooth surface and uniform distribution, and have good monodispersity. Figure 2 As can be seen in (c), under the action of CTAC, TEA and BTES, the surface of SiO2 microspheres is evenly coated with a layer of organic silicon shell, and there are mesopores on the surface of the silicon shell (as shown in the inset). Figure 2 (d) It can be seen that the internal SiO2 core is completely removed, forming a HMON with a hollow mesoporous structure, whose edge contour morphology is clear and the sphericity is complete and uniform. In the high-magnification TEM image ( Figure 2 e, f) It can be seen that the microspheres in front and behind the lens overlap with each other, and the morphology of the microspheres in the back can be seen from the microspheres in the front, indicating that the prepared HMON is a monodisperse hollow mesoporous microsphere with no adhesion on the surface, which is consistent with the results reflected by SEM.
[0064] HMON-garlic NPs were formed by loading garlic NPs inside HMON. The enzyme response system was constructed by modifying the lignin CQDs on the surface of HMON-garlic NPs. Figure 3 These are TEM images at different synthesis stages. Figure 3 (a) shows the microscopic image of HMON-garlic NPs formed after HMON microspheres were loaded with garlic NPs. As can be seen from the figure, the outline of HMON is clearly visible, garlic NPs fill the cavity inside the microspheres, and the outer surface of the formed HMON-garlic NPs is smooth. Figure 3(b, c) are TEM images of the synthesized response system HMON-garlic NPs-CQDs. TEM shows that the cavity inside the microsphere is still black, indicating that the blocking of lignin CQDs does not cause the preservative garlic NPs to leak out of the microsphere. At the same time, it can be clearly observed that the outer surface of HMON-garlic NPs is coated with a thin film, or similar to forming a thin polymer coating. Figure 3 (b, c) show that HMON-garlic NPs-CQDs can encapsulate garlic NPs inside the microspheres, and CQDs can block the pores on the surface of HMON to prevent the massive leakage of garlic NPs. Figure 3 This provides direct evidence for the distribution of lignin CQDs on the surface of HMON-garlic NPs.
[0065] In order to explore the in vitro antibacterial effect of HMON-garlic NPs-CQDs, the PDA plate antibacterial method was used, combined with the growth rate of Coriolus versicolor, to evaluate the antifungal effect of the nanoparticles. In the in vitro antibacterial test, different concentrations of agents were selected to inhibit the growth of Coriolus versicolor, and then the effective antibacterial concentration was screened. Figure 4 The growth trend of Coriolus versicolor is shown. As can be seen from the figure, the mycelium of the blank group secretes vigorously, indicating that it has a high secretion activity. Different concentrations of HMON-garlic NPs-CQDs were added to the PDA medium to prepare the poisoned medium. Different concentrations of the poisoned medium had an inhibitory effect on Coriolus versicolor. As the concentration increased, the inhibitory effect on Coriolus versicolor was more obvious, its growth was gradually inhibited, and the diameter of the bacterial circle gradually decreased. Through in vitro antibacterial tests, the effective antibacterial concentration of the preservative HMON-garlic NPs-CQDs was 50 mg / mL.
[0066] For the corrosion resistance test, the impregnation of enzyme-responsive preservative HMON-garlic NPs-CQDs in wood specimens was investigated. Figure 5 The SEM images showing the distribution of HMON-garlic NPs-CQDs inside the wood specimens. Figure 5 (a, d, j) are three sections of the blank group wood samples. From the figures, we can clearly see the wood hierarchical structure such as wood pores, vessel walls and pits, without the presence of other impurities. Figure 5 (b, c) are SEM images of HMON-garlic NPs-CQDs in wood at different magnifications. It can be observed from the images that some pores are blocked and there are many particles distributed around the pores. Figure 5 (e, f) and Figure 5(h, i) are the radial section and tangential section of the preservative-loaded sample, respectively. It can be seen that the tube wall is filled with more substances and the wood surface is no longer smooth. The SEM image shows that the enzyme-responsive preservative HMON-garlic NPs-CQDs can be distributed into the wood hierarchical structure.
[0067] After garlic NPs and HMON-garlic NPs-CQDs entered the interior of the wood specimens, specimens with similar drug loading were selected to analyze the leaching effects of garlic NPs and HMON-garlic NPs-CQDs when exposed to liquid water. Figure 6 The drug loading and loss rate of garlic NPs and HMON-garlic NPs-CQDs. As can be seen from the figure, the drug loading of garlic NPs and HMON-garlic NPs-CQDs increases with the increase of the drug concentration, and the leaching rate is negatively correlated with the drug loading. At the same concentration, the leaching rate of the response system HMON-garlic NPs-CQDs impregnated into the wood is lower than that of garlic NPs. This is caused by the encapsulation effect of HMON on garlic NPs and the blocking effect of lignin CQDs. The three-dimensional network structure of the hollow mesoporous silica microspheres improves the fixation effect of the preservative inside the wood sample, which reduces the leaching rate.
[0068] The antifungal effect of the enzyme-responsive preservative HMON-garlic NPs-CQDs is positively correlated with its concentration. The results of the corrosion resistance test show that HMON-garlic NPs-CQDs have an inhibitory effect on Coriolus versicolor. Garlic NPs can be released in response, thereby making the wood resistant to corrosion. The design of responsive preservatives can achieve the responsive release of preservatives and increase their fixation effect inside the wood. The successful construction of enzyme-responsive preservatives has expanded the application prospects of preservatives in the field of wood protection and provided new ideas for the sustainable development of modern forestry.
[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a carbon quantum dot modified enzyme-responsive wood preservative, characterized in that: The steps include: S1: Measure 12 mL of ultrapure water, 80 mL of anhydrous ethanol and 3.6 mL of concentrated ammonia solution, and stir for a preset time to fully mix them; Add 6.2 mL of TEOS, stir at room temperature for 2 h, centrifuge, take the precipitate, centrifuge and wash it three times with the preset liquid, dissolve the obtained precipitate SiO2 in 70 mL of ultrapure water to obtain SiO2 solution for use; Weigh 1.90 g CTAC and 0.05 g TEA and add them to 100 mL ultrapure water. Stir magnetically to fully dissolve them. Continue stirring for 2 h. Add 35 mL of the previously prepared SiO2 solution and stir magnetically. Then, add 2 mL of BTES to the above solution at 80 °C and stir for 2 h. Centrifuge for 5 min under the same conditions. Take the precipitate and wash it twice with the preset liquid in sequence. 0.6M Na2CO3 was added to the above solution and stirred at 80°C for 2h. The solution was washed three times by centrifugation at 8000r / min with a preset liquid. Finally, the solid product was extracted with a methanol solution dissolved in NaCl and stirred at room temperature overnight to remove the CTAC template. After centrifugal washing, the product was freeze-dried to obtain HMON nanoparticles. S2: Weigh 200.00 mg HMON nanoparticles, dissolve in 60 mL ultrapure water, and after uniform dispersion, add 450 μL APTES reagent, stir at room temperature for 10 h, centrifuge with ultrapure water three times, and freeze-dry to obtain amino-functionalized HMON-NH2; S3: Weigh 75.00 g of crushed garlic paste and dissolve it in 250 mL of ultrapure water and soak it for 2 h. Cook it at a preset temperature for 10 min and filter it with gauze to obtain a crude garlic extract. Mix 1 mL of garlic extract, 0.09 g of C2H8N2, 1.00 g of urea and 9 mL of ultrapure water and microwave it to obtain brown solid granular garlic NPs. S4: adding the garlic NPs prepared in S3 to ultrapure water, preparing a garlic NPs aqueous solution of a certain concentration with ultrapure water, dissolving HMON-NH2 in ultrapure water, dispersing evenly, adding to the garlic NPs aqueous solution, stirring at room temperature for 12 h, removing the supernatant after centrifugation, washing with ultrapure water for 3 times, and freeze-drying to obtain hollow mesoporous microspheres HMON-garlic NPs loaded with garlic NPs; S5: 60 mL of anhydrous ethanol was measured and placed in a 250 mL beaker, 2.15 g of dealkalized lignin was added, and the mixture was stirred at 1000 r / min for 10 min. After that, the mixture was evenly dispersed by ultrasound for 15 min, and the mixture was placed in a hydrothermal reactor for hydrothermal reaction to obtain a crude solution of carbon quantum dots. The solution was filtered 3 times to remove solid impurities, and the supernatant was filtered through a filter membrane after centrifugation. The filtrate was dialyzed with ultrapure water for 48 h, and then dried in a drying device to obtain lignin carbon quantum dots CQDs. S6: Weigh 0.30 g of HMON-garlic NPs powder obtained in S4, place it in a 500 mL beaker, add 200 mL of ultrapure water, and stir for 30 min. Dissolve 0.15 g of lignin carbon quantum dots in 100 mL of ultrapure water, disperse it evenly by ultrasonication, add it to the HMON-garlic NPs solution, and continue stirring at room temperature for 48 h. Synthesize the enzyme-responsive preservative HMON-garlic NPs-CQDs, and use lignin CQDs as a pore plugging agent to block the HMON surface.
2. The method for preparing a carbon quantum dot modified enzyme-responsive wood preservative according to claim 1, characterized in that: In S1, the centrifugal treatment has a centrifugal rate of 10000 r / min and a centrifugal duration of 5 min.
3. The method for preparing a carbon quantum dot modified enzyme-responsive wood preservative according to claim 1, characterized in that: In S3, the power of the microwave treatment is 500 W, and the centrifugation time is 5 min.
4. The method for preparing a carbon quantum dot modified enzyme-responsive wood preservative according to claim 1, characterized in that: In S4, the centrifugal treatment is carried out at a centrifugal rate of 8000 r / min and for a centrifugal time of 10 min.
5. The method for preparing a carbon quantum dot modified enzyme-responsive wood preservative according to claim 1, characterized in that: In S5, the centrifugal treatment is carried out at a centrifugal speed of 8000 r / min and a centrifugal time of 15 min.
6. The method for preparing a carbon quantum dot modified enzyme-responsive wood preservative according to claim 1, characterized in that: In S5, the drying equipment is a constant temperature drying oven, and the drying temperature of the constant temperature drying oven is 60°C.
7. The method for preparing a carbon quantum dot modified enzyme-responsive wood preservative according to claim 1, characterized in that: In S5, the filtering accuracy of the filter membrane is 0.22 μm.
8. The method for preparing a carbon quantum dot modified enzyme-responsive wood preservative according to claim 1, characterized in that: In S1, the preset liquid includes ethanol and ultrapure water.
9. The method for preparing a carbon quantum dot modified enzyme-responsive wood preservative according to claim 1, characterized in that: In S1, the stirring time of the magnetic stirring is 1.5 h.
10. The method for preparing a carbon quantum dot modified enzyme-responsive wood preservative according to claim 1, characterized in that: In S5, the reaction temperature of the hydrothermal reaction is 180° C., and the reaction time is 8 hours.